Perinatal mortality in breech deliveries at Dr. Said%ito General Hospital, Yogyakarta - Sulchan Sofoewan, Sulchan Sofoewan (Universitas Gadjah Mada, 1997)
Breech delivery is still of importance to discuss, because perinatal morbidity and mortility are higher than those vertex deliveries. A retrospective study was carried out on 141 cases of breech deliveries in Dr. Sardjito General Hospital during 1989 - 1990. The highest perinatal mortality was due to low birth weight: 17 cases (12%) compared to all cases (4.2%). No perinatal mortality of multiparity cases was found compared with cases of nulliparity i.e. 13 cases (17.0%). The type of breech presentation were frank breech: 85 cases (60.3%); incomplete: 21 cases (14.9%) and complete: 35 cases (24.8%). The highest perinatal mortality was frank breech presentation: 15 cases (17.6%). According to the termination of delivery, breech extraction has the highest perinatal mortality (23.%).Key Words: breech presentation - parity - perinatal - morbidity - mortality